2012
DOI: 10.7860/jcdr/2012/4137.2363
|View full text |Cite
|
Sign up to set email alerts
|

A Ten Year Retrospective Study on Adult Tetanus at the Epidemic Disease (ED) Hospital, Mysore in Southern India: A Review of 512 Cases

Abstract: Background: Tetanus still remains a major public health problem in India like in most other developing countries, with a high morbidity and mortality.Objectives: To study the socio-demographic profile and the clinical profile that they presented with, as well as the outcome of the tetanus patients who were admitted to the E.D Hospital, Mysore in India. Methodology:The data of all the patients of tetanus who were above the age of 15 years, who were admitted from January 2001 to December 2010, were collected, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
23
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 8 publications
8
23
0
4
Order By: Relevance
“…With the establishment and development of critical care medicine in China, the mortality rate of tetanus in 2015 had decreased by approximately 93.54% compared with that in 1990 [1]. In our study, only 5 adults (5.26%) died from tetanus, which was basically the same as the mortality rate in developed countries and significantly lower than that in other developing countries [1,4,17]. Nonetheless, the small number of patients included in this study cannot well reflect the current situation of tetanus in China, and more clinical studies should be performed in the future.…”
Section: Biomed Research Internationalsupporting
confidence: 56%
See 1 more Smart Citation
“…With the establishment and development of critical care medicine in China, the mortality rate of tetanus in 2015 had decreased by approximately 93.54% compared with that in 1990 [1]. In our study, only 5 adults (5.26%) died from tetanus, which was basically the same as the mortality rate in developed countries and significantly lower than that in other developing countries [1,4,17]. Nonetheless, the small number of patients included in this study cannot well reflect the current situation of tetanus in China, and more clinical studies should be performed in the future.…”
Section: Biomed Research Internationalsupporting
confidence: 56%
“…It is necessary to further standardize treatment with TAT. Only 9 patients in our study received HTIG treatment, and the proportion was much lower than that in other countries [4,17,18]. Although it is believed that the use of human or equine antitoxins (TAT and HTIG) does not change the mortality rate of tetanus, HTIG has a longer half-life in the body and causes fewer adverse reactions [14].…”
Section: Biomed Research Internationalmentioning
confidence: 79%
“…Mostly patients acquired tetanus following trauma which was mainly due to working bare footed in the fields and road traffic accidents. 7,8 In present study overall mortality rate is 16.5% which is quite consistent with the observation reported by Younas at el (18%) and Kole et al (21.6%), whereas Anuradha and Marulappa et al had reported higher mortality rate, 37.78%, and 42.2% respectively. [7][8][9][10] The present study observed that overall mortality due to tetanus was much lower compared with other Indian studies due to timely and proper management.…”
Section: Discussionsupporting
confidence: 90%
“…Tourniquet, whenever applied on the spot, should be released only in hospital settings and after starting antivenin 2. Features in favour of tetanus (mortality of 10–60%) include incubation period, symptomatology and isolation of organism in the background of incisions and cow dung application 3. This patient had a high possibility of developing gas gangrene as well.…”
Section: Descriptionmentioning
confidence: 95%